Optimal shari’ah governance model in Islamic finance regulation - Hasan, Aznan; sabirzyanov, Ruslan (Contemporary Research Center CRC Publications, 2015)
The Shari’ah governance is unique for Islamic financial institutions (IFIs), as it ensures that all activities of IFIs are in accordance with Shari’ah principles. At present, practices of Shari’ah governance in Islamic financial services industry vary from one jurisdiction to another. Nevertheless, three main Shari’ah governance models can be distinguished within this variety, namely, centralised, self-regulation and hybrid model. Today more and more countries are moving towards having a dedicated regulation to address Shari’ah governance framework, whereas a particular Shari’ah governance model will be chosen. This paper emphasises that Shari’ah compliance is the core element of Islamic finance and thus Shari’ah governance is a key factor to ensure such adherence. Furthermore, it advocates that the credibility of Shari’ah governance system and its effectiveness play vital role in the level of public confidence in Islamic finance. Having Central Shari’ah Board (CSB) with Shari’ah Supervisory Board (SSB) or only SSB was used as a distinguishing factor in classification of Shari’ah governance models. Each model of Shari’ah governance has its own advantages and disadvantages and these will be discussed in this paper. Subsequently, this paper proposes an optimal Shari’ah governance model to strengthen the weak aspects of the existing models.